RICH: Strategy-proof and efficient coflow scheduling in non-cooperative environments. (15th December 2021) - Zhang, Fan; Tang, Yazhe; Shan, Danfeng; Wang, Huanzhao; Hu, Chengchen
Abstract: Coflow scheduling can effectively improve the application performance and has been studied a lot in cooperative environments (e.g., private datacenter networks), where fairness is not the primary concern. In non-cooperative environments (e.g., multi-tenant datacenter networks), coflow scheduling should be strategy-proof; otherwise, some tenants could unfairly acquire more resources by cheating the scheduler. As minimizing coflow completion time (CCT) must prioritize coflows based on some specific rules (e.g., shortest-coflow-first, smallest-effective-bottleneck-first), tenants can raise the priority of their coflows by lying about the coflow information. Thus, it is a common belief that optimizing coflow performance can inevitably violate strategy-proofness. In this paper, we argue that the average CCT can be reduced without violating strategy-proofness. Our key insight is that prioritization can inherently achieve better CCT even without those specific rules such as smallest-effective-bottleneck-first. We propose RICH, a coflow scheduler in non-cooperative environments. At its heart, RICH splits the time into multiple rounds. In each round, RICH ensures that the total data transmitted by each tenant can provide optimal isolation guarantee. Among different rounds, RICH prioritizes coflow transmission among tenants in a round-robin manner. In this way, all tenants are fairly prioritized, and tenants do not necessarily gain more bandwidth by cheating. Extensive simulations show that RICH outperforms other strategy-proof mechanisms by up to 39.3% in terms of average CCT.